Pulp Regeneration: Current Approaches and Future Challenges - Yang, Jingwen; Yuan, Guohua; Chen, Zhi (Frontiers in Physiology, 2016)
Regenerative endodontics aims to replace inflamed/necrotic pulp tissues with regenerated pulp-like tissues to revitalize teeth and improve life quality. Pulp revascularization case reports, which showed successful clinical and radiographic outcomes, indicated the possible clinical application of pulp regeneration via cell homing strategy. From a clinical point of view, functional pulp-like tissues should be regenerated with the characterization of vascularization, re-innervation, and dentin deposition with a regulated rate similar to that of normal pulp. Efficient root canal disinfection and proper size of the apical foramen are the two requisite preconditions for pulp regeneration. Progress has been made on pulp regeneration via cell homing strategies. This review focused on the requisite preconditions and cell homing strategies for pulp regeneration. In addition to the traditionally used mechanical preparation and irrigation, antibiotics, irrigation assisted with EndoVac apical negative-pressure system, and ultrasonic and laser irradiation are now being used in root canal disinfection. In addition, pulp-like tissues could be formed with the apical foramen less than 1 mm, although more studies are needed to determine the appropriate size. Moreover, signaling molecules including stromal cell derived factor (SDF-1α), basic Fibroblast Growth Factor (bFGF), Platelet Derived Growth Factor (PDGF), stem cell factor (SCF), and Granulocyte Colony-Stimulating Factor (G-CSF) were used to achieve pulp-like tissue formation via a cell homing strategy. Studies on the cell sources of pulp regeneration might give some indications on the signaling molecular selection. The active recruitment of endogenous cells into root canals to regenerate pulp-like tissues is a novel concept that may offer an unprecedented opportunity for the near-term clinical translation of current biology-based therapies for dental pulp regeneration.